Antibacterial and antifungal activities of extracts of Zanthoxylum chalybeum and Warburgia ugandensis, Ugandan medicinal plants - Olila, D.; Odyek, Olwa; Opuda, Asibo J. (African Health Sciences, 2001)
Measles is a killer disease of children in Uganda. The treatment of the disease is mainly directed at the secondary microbial infections. A large proportion of the population in Uganda still relies on the use of herbal remedies, which have been claimed to produce beneficial responses. In this study, the efficacy of Warburgia ugandensis and Zanthoxylum chalybeum against common bacteria and fungi was investigated. Bactericidal and antifungal assays were done using extracts derived from Z. chalybeum and W. ugandensis (agar well diffusion, disc diffusion and colony count assays). All extracts (ethanolic, petroleum ether and aqueous) of Z. chalybeum did not show antimicrobial activity. Phytochemical investigations of Zanthoxylum chalybeum (seed) yielded a pure crystalline alkaloid (27-135D) which was characterized as skimianine based on 1H-NMR spectroscopy and comparison with spectra of authentic samples. Skimmianine did not have antimicrobial activity in this test system. W. ugandensis water extracts elicited antibacterial activity against both Escherischia coli and Staphylococcus aureus in the agar well assay but not in the disc diffusion assay. Warburgia ugandensis water extracts and fraction 27-163D also showed antifungal activity against Candida albicans. Chromatography of extracts of Warburgia ugandensis stem bark afforded compound 49-169K, which was characterized as the sesquiterpine muzigadial (by 1H-NMR spectroscopy), which did not show antibacterial activity but had antifungal activity against C. albicans. Therefore, the claimed efficacy of W. ugandensis could be attributable to antibacterial and antifungal activity of its components
Keywords: Antibacterial; Antifungal activities; Zanthoxylum chalybeum; Warburgia ugandensis; Medicinal plants